THE ROLE OF DIFFERENT EXERCISES IN IRISIN, HEAT SHOCK PROTEIN 70 AND SOME BIOCHEMICAL PARAMETERS: Role of Exercise on Irisin and Heat Shock Protein 70 - Akbulut, Taner; Cinar, Vedat; Aydin, Suleyman; Yardim, Meltem (Journal of Medical Biochemistry, 2021)
Background: The aim of the study was to determine the effects of different and regularly applied exercise programs on irisin, heat shock protein 70 and some biochemical parameters. Methods: 120 male university students participated in the study. Participants were divided into 4 equal groups as control (C), resistance exercise group (RE), high intensity interval (HIIT) and aerobic exercise group (AE). While the control group did not perform any exercise, the pre-determined exercise programs were applied to the other groups for 8 weeks and 3 days in a week. Blood samples were taken from all participants before and after the exercise program. Cholesterol, High-density Lipoprotein (HDL) and Low-density Lipoprotein (LDL) cholesterol, triglyceride (TG), creatine kinase (CK), lactate dehydrogenase (LDH), Irisin and Heat shock protein 70 (HSP70) levels were analyzed in blood samples. Results: It is determined that there are significant differences in pre-posttest values of the AE group’s LDH, cholesterol, HDL-cholesterol, TG and HSP 70 levels, HIIT group’s CK, LDH, Cholesterol, HDL-cholesterol, TG, Irisin and HSP70 levels and RE group’s CK, LDH, Cholesterol, LDLcholesterol, TG and irisin levels (p<0.05). Conclusions: It can be said that; exercise can provide improvements in lipid profile, changes in HSP70 levels may vary depending on muscle damage, the increase of irisin due to exercise.